Improving the Process of Understanding the Representation of Spatial Shapes Through the Problem-Based Learning Model Assisted by Ethnomathematics in Junior High School Students - Sika Sika; Mohd Fakri Muda; Mohd Razmi Zainudin; Nanang Diana; Mariamah Mariamah; Syarifudin Syarifudin; Muslim Muslim (Universitas Pendidikan Mandalika, 2026)
This study examines the comparative improvement in junior high school students’ understanding of spatial shape representation through the implementation of the Problem-Based Learning (PBL) model assisted by Ethnomathematics. The study employed a quasi-experimental Non-Equivalent Control Group Design involving 60 seventh-grade students at a junior high school in Bima Regency, consisting of an experimental class (n=30) and a control class (n=30). The intervention was conducted over four weeks through learning activities integrating local Bima cultural contexts, such as Uma Lengge vernacular architecture, into problem-solving and group discussion activities related to spatial geometry concepts. Pretest results indicated relatively comparable initial abilities between the experimental class (M=59.53) and the control class (M=59.00), while posttest results showed higher achievement in the experimental class (M=81.03) compared to the control class (M=69.97). An independent samples t-test yielded t=4.699 with p<0.001, indicating a statistically significant difference between the two groups. N-Gain analysis showed a moderate improvement in the experimental class (0.557) and a low improvement in the control class (0.272). Furthermore, Cohen’s d effect size analysis produced a value of 1.213, indicating a large practical effect. The findings suggest that integrating ethnomathematics within the PBL framework may support students in connecting cultural representations with mathematical concepts and contribute to the development of culturally contextualized mathematics learning in junior high schools.